Transition-metal-free [3+3] annulation reaction of sulfoxonium ylides with cyclopropenones for the synthesis of 2-pyrones - Maoyao He; Yuncan Chen; Yi Luo; Jianglian Li; Ruizhi Lai; Zengbao Yang; Yuerong Wang; Yong Wu (Green Synthesis and Catalysis, 2020)
An efficient and practical synthetic approach was developed for the tandem synthesis of trisubstituted 2-pyrone derivatives from sulfoxonium ylides and cyclopropenones. This [3+3] annulation reaction was carried out under transition-metal-free conditions. A broad range of functional groups were tolerant under mild conditions, and a variety of 2-pyrones were obtained in moderate to good yields.